2003
DOI: 10.1046/j.1472-765x.2003.01372.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and involvement in bread spoilage of Bacillus strains isolated from flour and ropy bread

Abstract: Aims: To study Bacillus contamination of wheat flour and ropy bread, to analyse genetic diversity of isolated strains and to evaluate the ability of these strains to produce ropy bread. Methods and Results: Classical and molecular methods [16S rDNA sequencing and random amplified polymorphic DNA (RAPD)-PCR] were used to identify and type-isolated strains. The predominant species isolated were Bacillus subtilis and B. licheniformis. RAPD analysis demonstrated that the same sample may harbor different strains. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
2
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 13 publications
1
48
2
1
Order By: Relevance
“…Additionally, a number of studies have reported the identification of spoilage Bacillus spp. identified here (e.g., B. cereus, B. licheniformis, B. subtilis, and B. weihenstephanensis) in nondairy foods, including bread, liquid eggs, seafood, and sous vide products, further illustrating the importance of spore-forming bacilli in our food system (16,20,44,83).…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, a number of studies have reported the identification of spoilage Bacillus spp. identified here (e.g., B. cereus, B. licheniformis, B. subtilis, and B. weihenstephanensis) in nondairy foods, including bread, liquid eggs, seafood, and sous vide products, further illustrating the importance of spore-forming bacilli in our food system (16,20,44,83).…”
Section: Discussionmentioning
confidence: 98%
“…and has been involved in food-poisoning incidents [9,10]. Some strains of this taxon were shown to produce a nonproteinaceous toxin, showing physicochemical properties similar to cereulide, the emetic toxin of Bacillus cereus [8].…”
Section: B Licheniformis Contaminates Industrial Processes [5^7]mentioning
confidence: 99%
“…The spores of B. amyloliquefaciens are well-known contaminants of raw materials used in bread making (ROSENKVIST;HANSEN, 1995;SOROKULOVA et al, 2003), and the spores can potentially even survive the bread baking process (VALERIO et al, 2015). Valerio et al (2012) found B. amyloliquefaciens to be the main species isolated from an outbreak of ropy bread spoilage in southern Italy.…”
Section: Introductionmentioning
confidence: 99%